Co-processing of palm fatty acid distillate and light gas oil in pilot-scale hydrodesulfurization unit over commercial CoMo/Al2O3. (1st July 2017) - Boonyasuwat, Sunya; Tscheikuna, Jirdsak
Highlights: Heat effect due to highly exothermic reactions was detected especially when the reactor handled higher PFAD in LGO. The dramatic increase in the reactor temperature when processing 25 wt% of PFAD in LGO almost reached the maximum operating and design temperature that the addition of PFAD exceed than this amount must be aware of any mechanical failure of the reactor. The increase in the reaction temperature slightly facilitated deoxygenation, but decreased desulfurization. Both reaction activities were at high ranges enough to meet the EN590 (EURO 4) specification for diesel fuel. Product quality as cetane was increased with the presence of PFAD in LGO as a result of the lower in the product density due to the additional of normal paraffin hydrocarbons which were mainly n-C15 to n-C18 . The hydrogen consumption for hydrotreating of PFAD was linearly increased with higher amount of PFAD, and the extrapolation to pure PFAD showed that the consumption required 344 Nm 3 /m 3 which was 24 times higher than that of LGO. Moreover, the additional consumption of 44 Nm 3 /m 3 was observed due to CO and CO2 methanation, reversed water gas shift and purged gas line to balance hydrogen purity in the system. Abstract: The effect of the presence of palm fatty acid distillate (PFAD) during co-processing with light gas oil (LGO) in hydrodesulfurization unit has been carried out in a near adiabatic, pilot-scale, and fixed-bed hydrotreating reactor, over commercial CoMo/Al2 O3 under 280–350 °C, 25 barg, H2 /feed ratio of 630 Nm 3 /m 3 and 0.75 h −1 . The amount of PFAD 5, 8, 12, and 25 wt% of PFAD in LGO was the feed mixtures. High conversion range on both desulfurization and deoxygenation reactions were achieved by every fraction of PFAD. The hydrocarbon products contained sulfur lower than 50 ppmw and neutralization number lower than 0.1 mg KOH/g. These products can be claimed as EURO 4 diesel following EN 590. The presence of PFAD in LGO improved the cetane index of the liquid products while lowered the product density. Highly heat effect was observed by an increasing of the reactor temperature up to 62 °C at the reactor outlet in the case of 25 wt% of PFAD. The increasing of the reactor temperature was resulting from an increasing amount of PFAD in LGO. The higher amount of PFAD slightly facilitated deoxygenation reaction, but impeded hydrodesulfurization reaction. The temperature rise also increased hydrocracking reaction evidenced by the lower contribution of total n-paraffin to the product mixture at higher PFAD in LGO. Finally, the hydrogen consumption was observed as linearly increased with an increasing amount of PFAD. The consumption was then theoretically calculated and extrapolated for hydrotreating of pure PFAD at 300 and 344 Nm 3 /m 3, respectively. An additional hydrogen consumption of 44 Nm 3 /m 3 was studied and discussed.